2021
DOI: 10.1021/acsanm.0c03387
|View full text |Cite
|
Sign up to set email alerts
|

CeO2 Nanoparticle Transformation to Nanorods and Nanoflowers in Acids with Boosted Oxidative Catalytic Activity

Abstract: Nanoceria (CeO2 nanoparticle) with oxidase-like catalytic activity has been used for a diverse range of analytical, environmental, and nanomedicine applications. In this work, the use of nanoceria for the oxidation of common chromogenic substrates was investigated at low pH, where its activity was greatly enhanced. In addition, the shape of the nanoparticles changed dramatically, yielding nanorods in the presence of adsorbed substrates at pH 1. This work provides an interesting method to synthesize CeO2 nanoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 63 publications
(107 reference statements)
0
13
0
Order By: Relevance
“…96,157 In general, the morphologically dependent catalytic activities of CeO 2 NMs are best examined by selectively synthesizing them with different crystal surfaces. It is widely accepted that there are several ways to synthesize 3D CeO 2 nanostructures, including hydrothermal methods, 102 selfassembly at room temperature, 75 electrochemical deposition, 125 and template methods. 114 Changing the hydrothermal conditions can produce different CeO 2 NP structures.…”
Section: D Ceomentioning
confidence: 99%
See 1 more Smart Citation
“…96,157 In general, the morphologically dependent catalytic activities of CeO 2 NMs are best examined by selectively synthesizing them with different crystal surfaces. It is widely accepted that there are several ways to synthesize 3D CeO 2 nanostructures, including hydrothermal methods, 102 selfassembly at room temperature, 75 electrochemical deposition, 125 and template methods. 114 Changing the hydrothermal conditions can produce different CeO 2 NP structures.…”
Section: D Ceomentioning
confidence: 99%
“…A significant part of the surface catalytic reaction and/or chemoselectivity of CeO 2 NMs is determined by their morphology, which presents different spatial dimensions, morphologies, OV concentrations, crystallinities, and specific surface areas . At present, the common synthesis of CeO 2 NMs mainly includes traditional synthesis methods (e.g., hydrothermal methods, , precipitation, ,,, thermal decomposition, spray pyrolysis, sol–gel methods, , and green synthesis , ). Green synthesis is a synthesis method mediated by plant extracts (e.g., Jatropha curcas extract and Rhus punjabensis).…”
Section: Synthesis Of Ceo2 Nmsmentioning
confidence: 99%
“…Consequently, in vivo use of MOF-Au-Ce in the treatment of S. aureus-induced subcutaneous abscess in mice enhanced wound healing and proved bacteriostatic [257]. The cerium oxide nanoparticle (nanoceria) was shown to possess high peroxidase activity [257,258]. Provided that high peroxidase activity is more conducive to promoting the production of ROS, the CeO 2 -H 2 O 2 system might be regarded generally a good solution for bacterial disinfection.…”
Section: Nanozymes Combating Pathogensmentioning
confidence: 99%
“…CeO 2 nanoparticles (nanoceria) are classical nanozymes that possess a diverse range of enzyme-mimicking activities. Nanoceria with a high fraction of Ce 3+ (and thus oxygen vacancies) usually has strong oxidative activity. Previous works reported that H 2 O 2 can quickly oxidize Ce 3+ to Ce 4+ on the surface of nanoceria at neutral pH, and the absorbed H 2 O 2 decomposes over a few days, indicating the stability of the H 2 O 2 –nanoceria complex. Furthermore, since the hydrolysis of Ce 4+ may lead to products similar to CeO 2 , it might be possible to use H 2 O 2 to synthesize nanoceria under physiological conditions and obtain in situ catalytic cascades.…”
Section: Introductionmentioning
confidence: 99%